Nutritional status in patients with advanced‐stage multiple sclerosis. (24th February 2022) - Teng, Maëlys; Bensmail, Djamel; Hanachi, Mouna; Haddad, Rebecca; Hugeron, Caroline; Lansaman, Thibaud; Levy, Jonathan
Abstract: Introduction: Motor and swallowing dysfunctions in multiple sclerosis (MS) unbalance calorie intake and energy expenditure, modifying nutritional status. Only one study has described nutritional status in MS patients at early disease stages (median Expanded Disability Status Scale [EDSS] = 3), but this has never been assessed in the most severe cases. The goal of the present study was to describe nutritional status in advanced‐stage MS. Methods: The study was a non‐interventional retrospective analysis of a prospective registry. We reviewed medical files of consecutive MS patients admitted for annual follow‐up in a physical and rehabilitation medicine unit between May 2016 and October 2018. Malnutrition for frail people, according to the French Health Authority (Haute Autorité de Santé [HAS]) definition, was our composite primary outcome criterion: body mass index (BMI) <21 kg/m 2 and/or albumin<35 g/L. First, we performed a descriptive analysis of the nutritional status. Second, we studied the association between malnutrition and MS characteristics in univariate and multivariate analyses. Results: A total of 163 patients with median EDSS = 8 [7; 8.5] were included. Ninety‐three patients (57%) met HAS malnutrition criteria (36% with albumin <35 g/L, 31% with BMI <21 kg/m 2 and 10% with both). Malnutrition was associated in univariate analysis with MS severity (EDSS ≥8.5, p  = 0.0003), primary progressive type of MS ( p  = 0.01) and swallowing disorders ( p  = 0.002). Multivariate analysis showed that low disability status (EDSS <7) was the only independent (protective) factor associated with malnutrition (OR = 0.2, p  = 0.03). Conclusions: Malnutrition is frequent in advanced stages of MS and is probably a key point for therapeutics, which has never been demonstrated previously. A standardized evaluation should be developed to improve nutritional therapeutic strategies in this population. Abstract : Our study shows high rates of malnutrition (from one third to one half) in patients in advanced stages of multiple sclerosis (MS), with a tendency for these individuals to be more underweight than the overall population. Albumin levels and weight loss may be pertinent and easy‐to‐use follow‐up markers. The lower the albumin levels, the higher the risk of pressure sores in the most disabled patients with MS.